Differences in the impact of land transfer on poverty vulnerability among households with different livelihood structures - Zhao, Xiaonan; Lan, Feng; Guo, Mengdan; Zhang, Liping (Frontiers in Sustainable Food Systems, 2024)
Introduction Eradicating poverty is the primary objective of the United Nations 2030 Agenda for Sustainable Development. While China has achieved great success in achieving poverty reduction targets, reducing the poverty vulnerability of rural households is crucial for ensuring the sustainability of poverty reduction gains. The purpose of land transfer is to ensure the continuous increase of farmers’ income through efficient land use; it has become an important initiative for poverty alleviation in rural areas. Existing studies have confirmed the positive effect of land transfer on poverty alleviation, but few have explored the difference in the impact of land transfer on poverty vulnerability of households with different income structures. Methods Using data from the China Family Panel Survey (CFPS) from 2010 to 2020, this paper empirically examines the impact of land transfer on poverty vulnerability. Results and discussion The results show that land transfer has a significant positive impact on poverty vulnerability alleviation among rural households. Further comparing households with different livelihood structures, we find that land transfer is more effective in reducing poverty for non-farm employment-oriented household. Therefore, we suggest that the government should improve the land transfer system, increase agricultural subsidies, and consider the occupational differentiation among farmers to improve the poverty reduction effect of land transfer. These suggestions also provide a reference for promoting sustainable agricultural development and consolidating the achievements of poverty alleviation.